1999
DOI: 10.1161/01.cir.100.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin in Cardiac Hypertrophy in Rats With Aortic Stenosis

Abstract: The neuregulin receptors erbB2 and erbB4 are downregulated at both the message and protein levels at the stage of early failure in animals with chronic hypertrophy secondary to aortic stenosis. These data suggest a role for disabled erbB receptor signaling in the transition from compensatory hypertrophy to failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 40 publications
2
46
1
Order By: Relevance
“…All 4 are expressed in the heart, with ErbB1, ErB2 and ErbB4 declining with postnatal development (Camprecios et al, 2011). Although earlier studies documented expression of ErbB1, ErbB2 and ErbB4 only in adult heart (Sundaresan et al, 1998;Zhao et al, 1998;Rohrbach et al, 1999), more recent work also confirms adult expression of ErbB3 (Lorita et al, 2009;Camprecios et al, 2011).…”
Section: The Egfr Familymentioning
confidence: 98%
See 1 more Smart Citation
“…All 4 are expressed in the heart, with ErbB1, ErB2 and ErbB4 declining with postnatal development (Camprecios et al, 2011). Although earlier studies documented expression of ErbB1, ErbB2 and ErbB4 only in adult heart (Sundaresan et al, 1998;Zhao et al, 1998;Rohrbach et al, 1999), more recent work also confirms adult expression of ErbB3 (Lorita et al, 2009;Camprecios et al, 2011).…”
Section: The Egfr Familymentioning
confidence: 98%
“…Cardiac ErbB2 and ErbB4 mRNA and protein levels increase with ventricular pressure overload during compensatory cardiac hypertrophy in mouse models, yet decline on transition to heart failure (Rohrbach et al, 1999). Subsequent work from these investigators showed reduced ErbB2 and ErbB4 expression and activity in patients with advanced heart failure (Rohrbach et al, 2005).…”
Section: Hypertrophy/heart Failurementioning
confidence: 99%
“…The negative inotropic actions of NRG-1 may also explain why the myocardium downregulates ErbB2 and ErbB4 at the onset of heart failure 13 in an attempt to augment contractile performance. NOS inhibition attenuated the effects of NRG-1 on myocardial contractility, whereas inhibition of the prostaglandin pathway had no effect.…”
Section: Lemmens Et Almentioning
confidence: 99%
“…9,15 The following antibodies were used to measure levels of LV proteins: antimuscarinic AChR-M 2 (Santa Cruz Biotechnology); anti-G protein subunits G␣ i1,2 , G␣ i3 , and G␣ o (Calbiochem); and anti-endothelial NO synthase (eNOS) and anti-inducible NO synthase (iNOS) (BD Biosciences). Protein levels of the nicotinic receptor AChR-␤ 1 (Santa Cruz Biotechnology) were investigated in brain lysates.…”
Section: Western Blottingmentioning
confidence: 99%
“…7,8 We demonstrated that left ventricular (LV) erbB2 and erbB4 protein levels are decreased in experimental heart failure 9 and that mice with conditional erbB2 mutation develop cardiomyopathy. 10,11 These data support the concept that neuregulin-erbB signaling is cardioprotective, but the responsible mechanisms are incompletely understood.…”
mentioning
confidence: 99%